2020
DOI: 10.1016/j.neuron.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Tipping the Scales: Peptide-Dependent Dysregulation of Neural Circuit Dynamics in Alzheimer’s Disease

Abstract: Identifying effective treatments for Alzheimer's disease (AD) has proven challenging and has instigated a recent shift in AD research focus towards the earliest disease-initiating cellular mechanisms. A key insight has been an increase in soluble Aβ oligomers in early AD that is causally linked to neuronal and circuit hyperexcitability. However, other accumulating AD-related peptides and proteins, including those derived from the same amyloid precursor protein, such as Aη or sAPPα, and autonomously, such as ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
156
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(175 citation statements)
references
References 203 publications
(202 reference statements)
16
156
0
3
Order By: Relevance
“…In conclusion, we demonstrate that both Aη peptides acutely regulate neuronal mechanisms ex vivo and in vivo and could thus represent important endogenous modulators of synapse communication. Our ndings provide further evidence that, beyond Aβ, APP cleavage products contribute to a rich array of effects on neuronal function 22 , which delicately maintains neuronal network homeostasis and may be uniquely susceptible to perturbation. For ex vivo electrophysiology recordings, experiments were conducted according to the policies on the care and use of laboratory animals stipulated by French ministry of research according to the European Communities Council Directive (2010/63).…”
Section: Discussionmentioning
confidence: 58%
“…In conclusion, we demonstrate that both Aη peptides acutely regulate neuronal mechanisms ex vivo and in vivo and could thus represent important endogenous modulators of synapse communication. Our ndings provide further evidence that, beyond Aβ, APP cleavage products contribute to a rich array of effects on neuronal function 22 , which delicately maintains neuronal network homeostasis and may be uniquely susceptible to perturbation. For ex vivo electrophysiology recordings, experiments were conducted according to the policies on the care and use of laboratory animals stipulated by French ministry of research according to the European Communities Council Directive (2010/63).…”
Section: Discussionmentioning
confidence: 58%
“…Taken all together, our work shows that chronic levetiracetam treatment in App KI mouse models normalizes levels of presynaptic endocytosis machinery and alters APP proteolytic processing corresponding with lower levels of Aβ 42 and decreased amyloid plaque deposits. As a growing body of evidence has demonstrated an association between AD and brain hyperexcitability, understanding the relationship between neural network dysfunction and Aβ pathology is crucial (Kuchibhotla et al, 2008, Bakker et al, 2012, Toniolo et al, 2020, Harris, et al, 2020, Sen et al 2018). Interestingly, in a study of AD patients with epilepsy, a comparison of levetiracetam versus typical epilepsy drugs, lamotrigine and phenobarbital, demonstrated that while all the drugs were equally effective in reducing seizures, only levetiracetam treatment led to improved performance on cognitive tasks (Cumbo et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in mouse models of MTLE and AD has established a feedforward cycle directly linking neuronal hyperactivity with excess release of soluble amyloid and tau, suggesting that epileptiform activity in AD drives further deposition of amyloid and tau pathology. 8 Treatment of hAPP J20 mice with levetiracetam not only reduced seizures and spiking but also ameliorated cognitive deficits, demonstrating that epileptiform activity can reversibly impact cognitive function in AD. 9 Moreover, hyperexcitability in mouse AD models can be rescued even while leaving amyloid plaques intact, 10 suggesting that stabilizing network excitability is possible even at later stages of AD and may still offer an important opportunity to protect cognitive function.…”
Section: Introductionmentioning
confidence: 97%
“…PET tracers that bind amyloid plaques and neurofibrillary tangles have transformed our ability to study AD pathology in vivo and correlate longitudinal changes in AD pathology with clinical features. 50 Since amyloid and tau deposition can both be driven by hyperactivity, 8 regional or lateralized tracer uptake could potentially indicate MTL network irritability. 18F-fluorodeoxyglucose (FDG) PET has clinical utility in both dementia and epilepsy but has not yet been evaluated in AD-related epilepsy.…”
Section: Introductionmentioning
confidence: 99%